Serum levels of vascular endothelial growth factor in patients with head and neck cancer - Riedel, Frank; Götte, Karl; Schwalb, Joachim; Wirtz, Heiner; Bergler, Wolfgang; Hörmann, Karl (European archives of oto-rhino-laryngology and head & neck, 2000)
Angiogenesis is now considered to be crucial for tumor growth and metastasis. In several tumors, microvascular density has been shown to be correlated with metastasis and aggressiveness. Vascular endothelial growth factor (VEGF) is a secreted endothelial cell-specific mitogen, which is induced by hypoxia and is angiogenic in vivo. VEGF has been identified in a wide variety of malignancies including head and neck squamous cell carcinomas (HNSCC). We investigated the circulating level of VEGF in sera from patients with various head and neck squamous cell carcinomas (n = 71) as well as from healthy normal controls (n = 47). Serum VEGF concentrations were determined as serum immunoreactivity by using a quantitative sandwich enzyme immunoassay technique. For statistical analysis, the Wilcoxon 2-sample test and Kruskal-Wallis test were performed. The majority of the patients with HNSCC were found to have high concentrations of serum VEGF. The levels of VEGF in the sera of patients with cancer ranged from below the detection limit to 937.1 pg/ml (mean, 144.5 pg/ml). In contrast, the VEGF serum levels in 47 healthy individuals ranged from below the detection limit to 168.1 pg/ml (mean, 32.7 pg/ml), VEGF serum concentration being significantly higher in HNSCC patients (P = < 0.001). These findings indicate that a positive angiogenesis regulator such as VEGF might function as an endocrine growth factor, particularly for solid HNSCC tumors and may be a useful marker for clinical monitoring.
Gesehen am 12.05.2022